2020
DOI: 10.1002/osp4.413
|View full text |Cite
|
Sign up to set email alerts
|

Relatively low sex hormone‐binding globulin concentration is a risk factor for hyperuricemia in middle‐aged Japanese men

Abstract: Summary Objective Low testosterone and hyperuricemia are associated with metabolic syndrome (MetS). However, little is known about the nature of the relationships between serum testosterone and sex hormone‐binding globulin (SHBG) concentrations, and hyperuricemia. Methods We evaluated the relationships between serum testosterone (calculated bioavailable testosterone [cbT], calculated free testosterone [cFT], SHBG, and total testosterone [TT]) and metabolic indices, including serum uric acid, in 363 Japanese ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…SHBG can also bind free androgens to reduce their levels and control their bioavailability to indirectly affect the UA concentration. Fujihara et al [ 42 ] suggested that a lower concentration of SHBG (46.5 nmol/L) was a predictor of hyperuricaemia, which may lead to reduced production of SHBG via induced inactivation of AMPK in the liver [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…SHBG can also bind free androgens to reduce their levels and control their bioavailability to indirectly affect the UA concentration. Fujihara et al [ 42 ] suggested that a lower concentration of SHBG (46.5 nmol/L) was a predictor of hyperuricaemia, which may lead to reduced production of SHBG via induced inactivation of AMPK in the liver [ 43 ].…”
Section: Introductionmentioning
confidence: 99%